Sharia Compliance, Religiosity, and Human Resource Blessings in Islamic Banking: Evidence from the Tawhidi String Relation Perspective - Noki Syafriadi; Tatik Mariyanti; Syofriza Syofyan (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study aims to analyze the influence of Sharia compliance implementation on the blessings of human resources, the influence of Sharia compliance implementation on religiosity, and the influence of religiosity on the blessings of human resources in Sharia Banking. The method used was a quantitative descriptive approach involving three variables and 90 indicators (reduced to 74 after validity testing), based on the Tawhidi String Relation (TSR) perspective. Data analysis was conducted using Factor Analysis to reduce the indicators and Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine causal relationships among the variables. The study involved 385 respondents consisting of employees, staff, and executives in Sharia Banking. The results show that Sharia compliance implementation has a positive influence on both the blessings of human resources and religiosity. Religiosity also has a positive influence on the blessings of human resources. In addition, Sharia compliance indirectly enhances the blessings of human resources through religiosity. This study highlights the importance of strengthening Sharia values implementation in banking products, transactions, and operations. Leaders are expected to serve as role models in applying an Islamic work culture in accordance with DSN-MUI fatwas and maqashid sharia. Support from shareholders and strengthening the role of the Sharia Supervisory Board are essential to ensure the consistent implementation of Sharia principles, thereby enhancing both spiritual and material blessings for human resources.